Ontologi Tuhan dan Kosmologi dalam Filsafat Peripatetik Islam: Komparasi Pemikiran Al-Farabi dan Ibnu Sina - Rini Lismeiliani; Lukman Hakim (Al-Widad, 2026)
Ideally, studies on the ontology of God and cosmology in Islamic Peripatetic philosophy should explain the conceptual continuity between the philosophical systems of Al-Farabi and Ibn Sina as an integrated intellectual tradition. In reality, however, most previous studies have examined these two philosophers separately or focused only on specific concepts without comprehensively analyzing the ontological and cosmological relationship between God and the universe. This study aims to comparatively examine the concepts of God and the cosmos in the thought of Al-Farabi and Ibn Sina and to explore their contributions to the development of Islamic metaphysics. This research employs a qualitative library research approach using comparative philosophical analysis. The primary data are derived from the original works of both philosophers, supported by relevant scholarly literature, and analyzed through content analysis and comparative analysis. The findings reveal that both philosophers share the same metaphysical foundation by positioning God as the First Being and the ultimate source of all existence, while differing in their philosophical orientation. Al-Farabi emphasizes the cosmological structure through the concept of al-Mawjūd al-Awwal, whereas Ibn Sina develops a more systematic ontology through the concept of Wājib al-Wujūd. These differences reflect the internal evolution of Islamic Peripatetic philosophy, culminating in a more comprehensive metaphysical system grounded in the principle of tawḥīd.